Mathematics

Question

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation. 15x − y = −6 5x − 3y = −13 5(−15x − 6) − 3y = −13 5(15x + 6) − 3y = −13 5x − 3(15x + 6) = −13 5x − 3(−15x − 6) = −13

2 Answer

  • 15x - y = - 6.....15x + 6 = y...so we sub in 15x + 6 in for y on the other equation

    5x - 3y = -13
    5x - 3(15x + 6) = -13 <== the new equation
  • Answer:

    Hence, the resultant equation will be:

    5x −3(15x + 6) = −13

    Step-by-step explanation:

    We are given a system of linear equations such that the first equation is given by:

    15x − y = −6------(1)

    and the second equation is given by:

    5x − 3y = −13----------(2)

    If you were to use the substitution method to solve the following system the new equation after the expression equivalent to y from the first equation is substituted into the second equation will be given by:

    consider equation (1)

    15x − y = −6------(1)

    find the expression in terms of x.

    i.e. 15x+6=y---(A)

    substitute this equation into equation (2) to obtain:

    5x − 3(15x + 6) = −13

NEWS TODAY